(3eLehY ef TYQ MGRe GdbQWGLfjs - (3MGRe GdbQWGLfj , MGRe Hf eMeO Hf MSf Hf MGRe, CHh GdMSf,J (B684 (3g` s ((3eMeO Hf SdjeGf Hf PcQj s)
(3ChdgG (B:s
(3YjO HLhOc LjOg bO obdOG hHojef LOc ojefog bO oCcOG s
(3BNQgG (B:s
(3hceG ofUQJ Ydi GdYOG ajeG eVi acPGc oJfUoQ aj GdReGf GdHGbj s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GfXQ aj GdeYgO Qbe (B1405 (3COHs
(3gfGc Tc aj UMI fSHI GdfGSN ddeNWhW h dYd cGJHgG gh cGJH ebUhQI MGRe GdeJbOeI aj GdeLehYI GdcJGH GdChd h gh eMeO Hf PcQj h gj Vef eLehYI GdcJGH GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B159s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B188 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs